Coastal vulnerability assessment for Selangor coastal, west coast of Malaysia using geospatial techniques / Amir Hafiz Mohd Rosli - Mohd Rosli, Amir Hafiz (2021)
The coast of peninsular Malaysia has a length of about 4,809 km. It shows that Malaysia have rich biodiversity and coastal resources. Therefore, the gift of natural wealth needs to be well preserved in order to last for generations to come. This paper aims to study the level of erosion and stagnation of the Selangor coast at the same time with the aim of assessing changes in coastal patterns and then explain the important erosion level factors in the study area. GIS technology and remote sensing have good accuracy rates with analysis and predictions that can be made to investigate this study. In this paper, both manual methods and coastal extraction processing have been investigated using multi-spectrum satellite imaging. The CVI consists of six variables, i.e. coastal geomorphology, coastal slope, rate of erosion and accretion, mean wave height, mean tidal range and sea level rise. Vulnerability levels for 8 management units along the Selangor coast are categorized into five vulnerabilities: very low, low, moderate, high and very high, based on the ratings of the above-mentioned mentis. The final results are a model to understand the level of change whether erosion or accretion in coastal research areas and the level of coastal vulnerability index for each management unit.